Evaluation index system for value co-creation in integrated care within the context of digital transformation - Chong Feng; Futian Weng; Liu Zhenyuan (Scientific Reports)
Abstract The significant impact of digital transformation on the co-creation of value in integrated care necessitates understanding its characteristics to enhance collaboration among healthcare organizations. The objective of this paper is to develop an evaluation index system for value co-creation in integrated care within the context of digital transformation. Utilizing Digital Business Ecosystem theory, the paper identifies the objectives, participating institutions, service processes, and expected outcomes of China’s integrated care, and constructs a comprehensive evaluation index system consisting of four primary indicators, 11 secondary indicators, and 47 tertiary indicators. These indicators evaluate value co-creation in integrated care across traditional healthcare value co-creation, digital value co-creation, healthcare structure, and output and quality dimensions. To address the issue of minimal value changes in some indicators within the study’s time frame, this paper proposes a modified entropy-weighted method to measure the comprehensive evaluation index of each dimension. This paper establishes an evaluation index system that provides a multi-level, systematic basis for examining the connotation and practical characteristics of integrated care value co-creation within the context of digital transformation.